Association ofClostridium difficileribotype 078 with detectable toxin in human stool specimens. Issue 11 (November 2015) - Fairley, Derek J.; McKenna, James P.; Stevenson, Mike; Weaver, Jeremy; Gilliland, Carol; Watt, Alison; Coyle, Peter V.
Abstract : N/A: Using a Clostridium difficile glutamate dehydrogenase (GDH) immunoassay and a sensitive C. difficile toxin A/B immunoassay, human stool specimens from patients with diarrhoea ( n = 1085) were classified as either GDH positive/toxin negative, or GDH positive/toxin positive. Overall, 528/725 (73%) of the GDH‐positive/toxin‐negative specimens contained viable C. difficile, and 433/528 (82%) of these C. difficile isolates were PCR positive for the toxin gene pathogenicity locus. Overall, 867/1078 (80%) of the GDH‐positive specimens contained viable C. difficile, and 433/725 (60%) of the GDH‐positive/toxin‐negative specimens contained a toxigenic C. difficile strain. The diversity of toxigenic C. difficile ribotypes isolated from toxin‐negative specimens ( n = 433) and toxin‐positive specimens ( n = 339) was significantly different ( P < 0.0001). Specifically, the presence of ribotype 078 strains was very strongly associated ( P < 0.0001) with detection of toxin in clinical specimens using a sensitive toxin immunoassay. Specimens positive for ribotype 078 were almost twice as likely to be toxin positive as opposed to toxin negative (risk ratio = 1.90, 95% confidence interval 1.64–2.19). In contrast, other circulating ribotypes were seen with similar frequency in specimens with and without detectable toxin. This supports the view that ribotype 078 strains may be more virulent than other common ribotypes in terms of toxin production.